Workshop Perpustakaan bagi Mahasiswa Baru sebagai Media Promosi Layanan di Perpustakaan IAIN Surakarta - Triningsih . (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2018)
AbstractLibrary has responsibility to introduce the product to every people. The mostof civitas academis is new students can to get and to know the product whichis in the college library. Avaibility the library workshop, it is to be the gateor the door of library to promote the service in it. The library workshop to bemeans introduce the library product. The method which to use is observationor direct observation with become a committee. The library workshopfor new students which is held by Library of IAIN Surakarta. The resultobtained are: 1) library profile; 2)library facility; 3)library utilization; 4)service procedures; 5)library rules. By looking at the workshop materials itcan be concluded that library workshop for new students is a media promotionservice in library. This paper is expected to provide inspiration thatpromotional activities are needed so that librarians can know the servicesin the library.AbstrakPerpustakaan mempunyai kewajiban untuk memperkenalkan produknyakepada masyarakat luas. Sivitas akademika terutama mahasiswa baruberhak mendapatkan dan mengetahui produk yang ada di perpustakaanperguruan tinggi. Adanya wokshop perpustakaan adalah menjadi gerbangatau pintu perpustakaan untuk mempromosikan layanan yang adadi dalamnya. Workshop perpustakaan menjadi sarana memperkenalkanproduk perpustakaan. Metode yang digunakan penulis dalam paparan iniyaitu observasi atau pengamatan langsung dengan terlibat menjadi panitiaWorkshop Perpustakaan bagi Mahasiswa Baru yang diselenggarakan oleh